Clinicians' views of factors influencing decision-making for CS for first-time mothers: a qualitative descriptive study - Daly, Deirdre; Panda, Sunita; Begley, Cecily (My University, 2022)
Clinicians’ perspectives of the reasons for performing caesarean section (CS) are fundamental to deepening knowledge and understanding of factors influencing decision-making for CS. The aim of this study was to explore midwives’ and obstetricians’ views of factors influencing decision-making for CS for first-time mothers. A qualitative descriptive study with semi-structured one-to-one audio-recorded interviews was used to gather data from clinicians (15 midwives and 20 senior obstetricians). Following research ethics committee approval, clinicians, who were directly involved in the decision-making process for CS during the period of data collection, were purposively selected from three maternity units in the Republic of Ireland between June 2016 to July 2017. The interviews were transcribed verbatim and analysed thematically. Three interrelated themes with several subthemes reflective of clinicians’ views and experiences emerged following data analysis. These were: ‘A fear factor’ describing clinicians’ fear of adverse outcomes and subsequent litigation, ‘Personal preferences versus a threshold–clinician driven factors emphasising the influence of clinicians’ personal beliefs, and ‘Standardised versus individualised care–a system perspective’ explaining the effects of, or lack of, organisational policy and its direct and indirect impact on the decision-making process. Findings show that decisions to perform a CS are, on occasion, based on clinicians’ personal beliefs and interpretation, similar to findings from other published literature. Consideration of broader issues related to organisational, socio-cultural and political context is essential when seeking solutions to the rising CS rates. The findings will enable clinicians to reflect on their day-to-day practice, in order to look for modifiable factors that influence their decision-making, and help women understand the multitude of factors that can lead to a decision to perform a CS. Findings will also contribute to the development of the ‘next step action’ and assist in devising future intervention studies to reduce any unnecessary CSs.
PUBLISHED
Keywords: CLINICAL DECISION MAKING; Caesaeran section; Clinicians' views; DECISION MAKING; MIDWIVES; Maternal Health; OBSTETRICIANS; QUALITATIVE RESEARCH